Formulasi sediaan body lotion dari ekstrak etanol buah bit (Beta vulgaris L.) sebagai pelembab kulit dan antioksidan - Tri Putri Ananda; Yessi Febriani; Sudewi Sudewi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background; Antioxidants are molecules that can prevent cell damage by free radicals. Beets (Beta vulgaris L.) are known to contain flavonoids which are antioxidants. This study aims to examine the antioxidant activity and skin moisturizing effect without skin irritation in a product formulated as a body lotion from the ethanol extract of beets (Beta vulgaris L.) at a certain concentration. Methods; This research was conducted using an experimental method using beetroot (Beta vulgaris L.) test material obtained by soaking 96% ethanol extract made in body lotion preparations with concentrations of 1.5%, 2%, 2.5% and blank samples. Sample and preparation tests included phytochemical screening, homogeneity test, inoculum pH test, emulsion type test, inoculum stability test, irritation test, water content test and antioxidant activity test. Result; The results showed that beet-based body lotion (Beta vulgaris L.) was a homogeneous preparation with an M/A emulsion and had a pH range immediately after preparation of 6.2 - 6.3 and a pH after cycle test was 6.2 - 6.3. Formula with a concentration of 2.5% (F3) is able to provide moisture in the wet category with a recovery rate of 27.74% lower than similar hand lotions that are applied to wet areas with a recovery rate of 28.18%. The ethanol extract of beets at a concentration of 2.5% (F3) had an IC50 valueof 118.101 µg/mL which indicated a moderate antioxidant class, while the ethanol extract of beets had an IC50 valueof 36.869 µg/mL which was classified as a very strong antioxidant. All body compositions based on ethanol extract of beetroot do not irritate the skin